(untitled) (Carte Romanze, 2019)
In this essay, thanks to the possibilities offered by digitalization of the five editions of Vocabolario degli Accademici della Crusca, of Tommaseo-Bellini and Grande dizionario della lingua italiana, together with the textual corpus of the Opera del Vocabolario Italiano (OVI-CNR), will be developed the diachronic and diatopic analisys of the circulation of rubro ‘bramble’, in its relationship with the latinism rubo and its vernacular variation rógo, in every different context that modify its meaning.